IoT Based Fetal Movement Counter with Fall Detector - Saaidan, Asma Diana; Nur Ilyani Ramli, (Evolution in Electrical and Electronic Engineering, 2023)
Fetal movements are an important factor in the assessment of fetal health. However, there is currently no reliable way to monitor fetal movement outside the clinical environment. This work aims to design a non-invasive portable device for fetal monitoring movement which able to detect and record all the fetal movement in the womb starting from 28 up until 40 weeks of gestation. Furthermore, during gestation, pregnant women have a high tendency to fall and this factor will affect the fetal and mother’s health. Falling during pregnancy will lead to severe injuries and negative pregnancy outcomes. This device uses a force-sensitive resistor (FSR) to count fetal movement, an ADXL335 accelerometer sensor to detect falls and an ESP32 as the microcontroller. When a pregnant woman feels fetal movement or kicking, they will touch the FSR sensor to record the beat counter. For fall detection, ADXL335 will detect whenever it senses unstable motions. Internet of Things (IoT) has also been implemented to this device using the Blynk application and they can monitor the readings using their mobile device. This portable device can help to trace and record fetal movement and detect falls. Pregnant women can use this dual-function portable device whenever they need and can help them to facilitate their fetal movement and fall detection performance.